ChemInform Abstract: A Route to α‐Fluoroalkyl Sulfides from α‐Fluorodiaroylmethanes. Issue 26 (June 2016) - Lin, Ya‐mei; Yi, Wen‐bin; Shen, Wan‐zhao; Lu, Guo‐ping
Abstract: α, α‐Difluorodiarylmethanes are successfully used as nucleophilic difluoromethylation reagents to generate α‐thioaryl‐α, α‐difluoroacetophenones or difluoromethylthiolated arenes from disulfides under transition‐metal free conditions.